Research on the impact of government digital infrastructure on urban economic resilience: a case study of the Yangtze River Delta urban agglomeration - Chen, Xiansheng; Liu, Lin; Zhang, Yaping; Xu, Longshun; Zheng, Changxu (Frontiers in Built Environment, 2026)
IntroductionAgainst the backdrop of the rapid development of the digital economy, information infrastructure has become a key support for enhancing the economic resilience of regions. Exploring the impact of digital infrastructure-related policies on urban economic resilience is of great significance for promoting regional high-quality development.MethodsTaking the Yangtze River Delta urban agglomeration as the research sample, this paper uses panel data of 27 cities from 2013 to 2022 and adopts the progressive difference-in-differences (DID) model to empirically examine the impact of the “Broadband China” policy on urban economic resilience. Robustness test methods including parallel trend test, placebo test, and PSM-DID are also employed to verify the reliability of the research conclusions.ResultsThe results show that the “Broadband China” policy significantly enhances the economic resilience of cities, with a robust positive effect. Mechanism analysis reveals that the policy indirectly boosts economic resilience through two channels: increasing government scientific spending and promoting the development of digital finance, demonstrating a logic of “resource optimization-innovation-driven financial empowerment”. Heterogeneity tests indicate that the policy effect is more pronounced in large cities and those with a favorable business environment. Robustness tests further validate the reliability of the conclusion.DiscussionThis study confirms that the construction of digital infrastructure not only enhances the resilience, recovery, and evolution capabilities of cities but also promotes high-quality economic development through informatization and innovation. The findings provide empirical evidence for improving government science and technology policies and promoting regional digital transformation.